2002
DOI: 10.1038/sj.bmt.1703608
|View full text |Cite
|
Sign up to set email alerts
|

Energy expenditure in children undergoing hematopoietic stem cell transplantation

Abstract: Summary:Prior studies suggest that patients undergoing hematopoietic stem cell transplantation (HSCT) for malignancy have nutritional needs that are greater than their estimated needs. To determine whether energy estimation equations accurately predict energy expenditure of pediatric patients undergoing HSCT, we prospectively compared the estimated energy expenditure (EEE) and measured energy expenditure (MEE) of 40 patients at four time-points. We also investigated whether energy requirements changed during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 18 publications
0
16
0
3
Order By: Relevance
“…Ayrıca beslenme destek tedavisi ile yaşam kalitesini yükseltmek ve normal büyüme-gelişmenin sağlanması amaçlanmaktadır. 8 KÖK HÜCRE NAKLİ HASTALARINDA BESLENME DURUMUNUN DEĞERLENDİRİLMESİ KHN sonrası hastalarda beslenme durumunun değerlendirilmesi oldukça zordur. Kemoterapi ya da enfeksiyonlardan dolayı immünolojik ölçümler hedef düzeyde olmamakta; biyokimyasal parametreler beslenme durumunu net olarak yansıtma-maktadır.…”
Section: Kök Hücre Nakli̇ çEşi̇tleri̇unclassified
See 2 more Smart Citations
“…Ayrıca beslenme destek tedavisi ile yaşam kalitesini yükseltmek ve normal büyüme-gelişmenin sağlanması amaçlanmaktadır. 8 KÖK HÜCRE NAKLİ HASTALARINDA BESLENME DURUMUNUN DEĞERLENDİRİLMESİ KHN sonrası hastalarda beslenme durumunun değerlendirilmesi oldukça zordur. Kemoterapi ya da enfeksiyonlardan dolayı immünolojik ölçümler hedef düzeyde olmamakta; biyokimyasal parametreler beslenme durumunu net olarak yansıtma-maktadır.…”
Section: Kök Hücre Nakli̇ çEşi̇tleri̇unclassified
“…DSÖ enerji harcaması denklemi ile ölçülen BMH değerinin, nakil sonrası 14. günde ancak gerçeği yansıttığı saptanmıştır. 8 Yapılan bir çalışmada, standart beslenme programlarının "refeeding" sendromuna neden olabileceği belirtilmiştir. 15 "Refeeding" sendromu, hastanın ihtiyacı olan enerji ve besin ögelerinden fazlasının verilmesiyle meydana gelen, vücutta sıvı artışına neden olarak kardiyak ve pulmoner güçlük yaratan ciddi bir komplikasyondur.…”
Section: Kök Hücre Nakli̇ Hastalarinda Enerji̇ Ve Makro Besi̇n öğEsi̇ İhtunclassified
See 1 more Smart Citation
“…In most cases it appears to be sufficient to restrict the amount of energy provided to be slightly more than the resting energy expenditure (see: Influence of malignancies on energy expenditure) [150], [151], [152]. …”
Section: Indications For Parenteral Nutrition During Autologous/allogmentioning
confidence: 99%
“…1 Among 25 subjects, weekly measurements of REE demonstrated normal energy expenditure prior to transplant with a decline over time, reaching a minimum at 4 weeks posttransplant of approximately 80% of predicted REE. Other studies have similarly found discrepancies between measured and estimated REE, 6,7 suggesting the need to employ indirect calorimetry to improve the accuracy of energy assessment. Monitoring REE is important but consumes time and resources and also represents some burden to the patients.…”
mentioning
confidence: 98%